2018
DOI: 10.1111/1742-6723.12948
|View full text |Cite
|
Sign up to set email alerts
|

Does respiratory variation of inferior vena cava diameter predict fluid responsiveness in spontaneously ventilating children with sepsis

Abstract: IVC collapsibility has poor test characteristics for predicting fluid responsiveness in spontaneously ventilating children with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
0
31
1
Order By: Relevance
“…23 However, in a study performed in septic pediatric patients, the ability of the CVCCI to discriminate between responders and nonresponders was poor, with an area under the ROC curve of 0.38 (95% CI, 0.23 to 0.55). 24 The differences with our study could be related to the different species and ages studied, as well as the underlying illnesses. Unlike the quoted study, 24 our study included a heterogeneous population with only few septic patients.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…23 However, in a study performed in septic pediatric patients, the ability of the CVCCI to discriminate between responders and nonresponders was poor, with an area under the ROC curve of 0.38 (95% CI, 0.23 to 0.55). 24 The differences with our study could be related to the different species and ages studied, as well as the underlying illnesses. Unlike the quoted study, 24 our study included a heterogeneous population with only few septic patients.…”
Section: Discussioncontrasting
confidence: 63%
“…In patients undergoing mechanical ventilation, the pooled sensitivity and specificity were 0.79 (95% CI, 0.67 to 0.86) and 0.70 (95% CI, 0.63 to 0.76), respectively 23 . However, in a study performed in septic pediatric patients, the ability of the CVCCI to discriminate between responders and nonresponders was poor, with an area under the ROC curve of 0.38 (95% CI, 0.23 to 0.55) 24 . The differences with our study could be related to the different species and ages studied, as well as the underlying illnesses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Variations in diameters of the SCV and IVC with respiration must be interpreted in the clinical context to make treatment decisions. 3,19,29,30…”
Section: Resultsmentioning
confidence: 99%
“…A meta‐analysis of 3 pediatric and 14 adult studies demonstrated moderate predictive value of IVC respiratory variation in spontaneously breathing and mechanically ventilated patients in acute circulatory failure with pooled sensitivity of 0.63 [95% confidence interval (CI) 0.56‐0.69], specificity of 0.73 (95% CI 0.67‐0.78), and area under the receiver operating characteristic curve of 0.79 (Figure ) . The test characteristics of IVC respiratory variation have been shown to perform better in mechanically ventilated patients (best in those with a tidal volume >8 mL/kg) as compared to spontaneously breathing patients . Due to the heterogeneity of the existing literature, there are insufficient data to inform accepted pediatric‐specific cutoffs to predict fluid responsiveness.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%